(untitled) (Research, Society and Development, 2020)
Throughout the last decades, spirituality has received prominence, including actions by the World Health Organization (WHO), which modified the multidimensional concept of health, formerly described as “a complete state of physical, mental and social well-being, and not only the absence of disease” to later “a dynamic state of complete physical, mental, spiritual and social well-being”. This article aims to discuss spirituality in undergraduate education as a possible tool for health education. It is an integrative review of the literature in databases, with the selection of 8 articles (6 international and 2 national), published among 2011 and 2016. Three thematic categories emerged: recognition of the importance of spirituality for patients; the lack of spiritual teaching in universities and the university as the cause of distance from spirituality. It was verified that spirituality has its importance recognized by students and professionals, but there is no consensus about its conceptualization and how it should be used in professional practice, which can be seen as a reflection of the academic formation. The difficulty is present in Psychology, Nursing, Medicine and related areas of Health Sciences. Therefore, researches on spirituality are justified by the gap still existing in the knowledge produced.